The Great Recession and Racial Inequality: Evidence from Measures of Economic Well-Being. Issue 4 (2nd October 2019) - Masterson, Thomas; Zacharias, Ajit; Rios-Avila, Fernando; Wolff, Edward N.
Abstract: The Great Recession had a tremendous impact on low-income Americans, in particular Black and Latino Americans. The losses in terms of employment and earnings are matched only by the losses in terms of real wealth. In many ways, however, these losses are merely a continuation of trends that have been unfolding for more than two decades. We examine the changes in overall economic well-being and inequality, as well as changes in racial economic inequality during and since the Great Recession. We find that the Levy Institute Measure of Economic Well-Being inequality between White and Black households decreased during the Great Recession but since 2010, racial inequality in terms of LIMEW has increased. We find that changes in base income, taxes, and income from non-home wealth during the Great Recession produced declines in overall inequality, while only taxes reduced between-group racial inequality.